Flight : riveting reads for curious kids - Grant, R. G. (Microbites., 2020)
Offers a brief, black-and-white illustrated history of flight. Explores the origins of human thought about flight with thinkers and inventors like da Vinci and the Wright Brothers up to modern planes, helicopters, blimps, and spacecraft.